Improving the cycle life of Li-metal batteries through metal / dielectric interface stacks
Patent Information
- Application Number
- JP2026512351
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-08-19
- Publication Date
- 2026-09-08
Smart Images

Figure 2026530460000001_ABST
Abstract
Description
[Technical Field]
[0001] background field
[0001] This disclosure relates, in general terms, to alkali metal-containing devices and methods for manufacturing alkali metal-containing devices. More specifically, this disclosure relates to device stacks including lithium metal anodes and prelithified anodes for energy storage devices, and methods for manufacturing them. [Background technology]
[0002] Description of related technologies
[0002] Rechargeable electrochemical energy storage systems are becoming increasingly indispensable in many aspects of daily life. High-capacity electrochemical energy storage devices such as lithium-ion (Li-ion) batteries are being used in an increasing number of applications, including portable electronic devices, medical devices, transportation equipment, grid-connected large-scale energy storage, renewable energy storage, and uninterruptible power supplies (UPS). Conventional lead-acid / sulfuric acid batteries often lack sufficient capacity and have inadequate cycle life to meet the growing demands of these applications. However, lithium-ion batteries are considered the best solution.
[0003]
[0003] Therefore, there is a need for methods and systems for depositing and processing lithium metal used in energy storage devices. [Overview of the project]
[0004]
[0004] This disclosure relates, in general terms, to alkali metal-containing devices and methods for manufacturing alkali metal-containing devices. More specifically, this disclosure relates to device stacks including lithium metal anodes and prelithified anodes for energy storage devices, and methods for manufacturing them.
[0005]
[0005] In one embodiment, an anode electrode structure is provided. The anode electrode structure includes a current collector made of copper and / or stainless steel, a lithium metal film formed on the current collector, and a protective film stack formed on the lithium metal film. The protective film stack includes a metal film formed on the lithium metal film and a lithium salt film formed on the metal film. The metal film is selected from a bismuth film, a tin film, a silver film, or a combination thereof. A lithium salt film is formed on the metal film, and the lithium salt film is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof.
[0006]
[0006] The implementation may include one or more of the following: The protective film stack further includes a lithium carbonate film, a lithium carbonate film formed on a lithium metal film, and a metal film formed on the lithium carbonate film. The anode electrode structure further includes an anode film, the anode film being formed on a current collector, and a lithium metal film being formed on the anode film. The metal film is a silver film. The metal film has a thickness in the range of about 50 nanometers to about 500 nanometers. The lithium salt film is a lithium fluoride film having a thickness in the range of about 100 nanometers to about 500 nanometers. The current collector includes a polymer substrate and a copper film formed on the polymer substrate.
[0007]
[0007] In another embodiment, an energy storage device is provided. The energy storage device includes the anode electrode structure, the cathode electrode structure, and a separator membrane or solid electrolyte membrane formed between the anode electrode structure and the cathode electrode structure.
[0008]
[0008] In yet another embodiment, a method for forming an anode electrode structure is provided. This method includes forming a protective film stack on a lithium metal film formed on a substrate. Forming the protective film stack includes forming a metal film on the lithium metal film and forming a lithium salt film on the metal film. The metal film is selected from bismuth film, tin film, silver film, or a combination thereof. The lithium salt film is selected from lithium sulfide, lithium oxide, lithium halide, chalcogenide lithium, lithium borohydride, or a combination thereof.
[0009]
[0009] The implementation may include one or more of the following: The method further includes forming a lithium carbonate film on a lithium metal film before forming a protective film stack on a lithium salt film, wherein the lithium carbonate film is formed on the lithium salt film and the metal film is formed on the lithium carbonate film. Forming the lithium carbonate film includes exposing the lithium metal film to CO2 gas in a first processing region defined by a first processing chamber. The method further includes transferring the substrate from the first processing region to the second processing region in a second processing region defined by a second processing chamber, wherein the protective film stack is formed in the second processing chamber. The substrate is a current collector having an anode film formed on the substrate. Forming the metal film includes a thermal evaporation process. Forming the lithium salt film includes a thermal evaporation process. The substrate is a web-based substrate. The metal film is a silver film. The metal film has a thickness in the range of about 50 nanometers to about 500 nanometers. The lithium salt film is a lithium fluoride film having a thickness in the range of approximately 100 nanometers to approximately 500 nanometers. The substrate includes a polymer substrate and a copper film formed on the polymer substrate.
[0010]
[0010] In yet another embodiment, a method for forming a film stack for an energy storage device is provided. The method includes forming a protective film stack on a flexible support layer stack. Forming the protective film stack includes forming a lithium salt film on a release layer, forming a metal film selected from a bismuth film, a tin film, a silver film, or a combination thereof on the lithium salt film, and forming a lithium metal film on the metal film. The method further includes laminating the lithium metal film onto a flexible substrate stack. The method further includes separating the protective film stack from the flexible support layer stack to form an anode film stack. The lithium salt film is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof.
[0011]
[0011] The mounting may include one or more of the following: A flexible support layer stack includes a polymer substrate having a release layer formed on the flexible support layer stack, and a protective film stack is formed on the release layer. The flexible support layer stack includes a polymer substrate, and the protective film stack is formed on the polymer substrate. A flexible substrate stack includes a current collector containing copper. The flexible substrate stack further includes an anode film formed on the current collector, and a lithium metal film is in contact with the anode film. Forming the metal film includes a thermal evaporation process. Forming the lithium salt film includes a thermal evaporation process. The metal film is a silver film.
[0012]
[0012] In yet another embodiment, an anode stack is provided. The anode stack includes a copper substrate configured to function as a current collector, a lithium layer disposed on the copper substrate and configured to function as an anode, a silver layer disposed on the lithium layer, and a lithium salt layer disposed on the silver layer, wherein the lithium salt layer is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof.
[0013]
[0013] The implementation may include one or more of the following: A passivation layer is placed between the lithium layer and the silver layer. The passivation layer contains lithium carbonate and is formed by passivating the lithium layer with carbon dioxide. The lithium salt layer contains lithium fluoride. The lithium salt layer has a thickness of 50 nm to 600 nm. The silver layer has a thickness of 40 nm to 600 nm.
[0014]
[0014] In yet another embodiment, a method for forming an anode stack is provided. This method comprises depositing a lithium layer on a copper substrate using a roll-to-roll physical vapor deposition (PVD) tool, depositing a silver layer on the lithium layer using thermal evaporation, and depositing a lithium salt on the silver layer using thermal evaporation, wherein the lithium salt layer is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof.
[0015]
[0015] The implementation may include one or more of the following: The method further includes passivating the lithium layer using an in-situ carbon dioxide passivation process before depositing the silver layer. The deposition and passivation of the lithium layer are performed in a roll-to-roll PVD tool, and the deposition of the silver layer and lithium salt layer is performed in different chambers. The method is performed in a roll-to-roll PVD tool. The lithium salt layer contains lithium fluoride. The lithium salt layer has a thickness of 50 nm to 600 nm. The silver layer has a thickness of 40 nm to 600 nm. The method further includes integrating the anode stack with the separator and cathode structure to form an energy storage device.
[0016]
[0016] In yet another embodiment, a method for forming an anode structure is provided. This method includes forming a release layer on a polymer substrate, depositing a lithium salt layer on the release layer disposed on the polymer substrate, depositing a silver layer on the lithium salt layer, depositing a lithium layer on the silver layer to form an anode, and transferring the anode from the polymer substrate to a copper substrate to form an anode structure, wherein the lithium salt layer is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof.
[0017]
[0017] The implementation may include one or more of the following: The lithium salt layer contains lithium fluoride. The lithium salt layer has a thickness of 50 nm to 600 nm. The silver layer has a thickness of 40 nm to 600 nm. The lithium layer has a thickness of 2 microns to 25 microns. The method further includes integrating the anode stack with the separator and cathode structures to form an energy storage device.
[0018]
[0018] In another embodiment, instructions are stored in a non-temporary computer-readable medium, and when executed by a processor, the operation of the apparatus and / or method is performed by a process.
[0019]
[0019] To understand the above-described features of the present disclosure in more detail, a more detailed description of the disclosure briefly summarized above can be obtained by referring to the embodiments shown in the accompanying drawings. However, it should be noted that the accompanying drawings show only exemplary embodiments and should not be construed as limiting the scope, and other equally valid embodiments are also possible. [Brief explanation of the drawing]
[0020] [Figure 1]
[0020] This is a schematic cross-sectional view of an energy storage device incorporating an anode structure having a protective film stack formed according to one or more implementations described herein. [Figure 2]
[0021] FIG. 1 is a cross-sectional view of a double-sided anode electrode structure having a protective film stack formed in accordance with one or more implementations described in the specification. [Figure 3]
[0022] FIG. 2 is a flowchart illustrating selected operations of a method of forming an energy storage device in accordance with one or more implementations of the present disclosure. [Figure 4A]
[0023] FIG. 3A illustrates various stages of manufacturing an energy storage device according to the method of FIG. 3, in accordance with one or more implementations of the present disclosure. [Figure 4B] FIG. 3B illustrates various stages of manufacturing an energy storage device according to the method of FIG. 3, in accordance with one or more implementations of the present disclosure. [Figure 4C] FIG. 3C illustrates various stages of manufacturing an energy storage device according to the method of FIG. 3, in accordance with one or more implementations of the present disclosure. [Figure 4D] FIG. 3D illustrates various stages of manufacturing an energy storage device according to the method of FIG. 3, in accordance with one or more implementations of the present disclosure. [Figure 5]
[0024] FIG. 4 is a flowchart illustrating selected operations of a method of forming an energy storage device in accordance with one or more implementations of the present disclosure. [Figure 6A]
[0025] FIG. 5A illustrates various stages of manufacturing an energy storage device according to the method of FIG. 5, in accordance with one or more implementations of the present disclosure. [Figure 6B] FIG. 5B illustrates various stages of manufacturing an energy storage device according to the method of FIG. 5, in accordance with one or more implementations of the present disclosure. [Figure 6C] FIG. 5C illustrates various stages of manufacturing an energy storage device according to the method of FIG. 5, in accordance with one or more implementations of the present disclosure. [Figure 6D] FIG. 5D illustrates various stages of manufacturing an energy storage device according to the method of FIG. 5, in accordance with one or more implementations of the present disclosure. [Figure 6E]This figure shows the various steps involved in manufacturing an energy storage device according to the method shown in Figure 5, in accordance with one or more implementations of the present disclosure. [Figure 6F] This figure shows the various steps involved in manufacturing an energy storage device according to the method shown in Figure 5, in accordance with one or more implementations of the present disclosure. [Figure 7]
[0026] The images show SEM images of lithium surfaces passivated with different protective film stacks and unpassivated control samples, according to one or more implementations of this disclosure. [Figure 8]
[0027] Plots of impedance data for various protective film stacks are shown according to one or more implementations of this disclosure. [Figure 9]
[0028] A voltage-versus-time graph illustrating the lithium plating / stripping behavior of Li / Li symmetric cells, including various protective film stacks, is shown according to one or more implementations of this disclosure. [Figure 10]
[0029] This graph plots the discharge capacity and charge capacity of Li / Li symmetric cells, collected according to one or more implementations of this disclosure, against the number of cycles. [Modes for carrying out the invention]
[0021]
[0030] To facilitate understanding, the same reference numerals are used for identical elements common to the figures whenever possible. It is believed that elements and features of one embodiment can be usefully incorporated into other embodiments without further explanation.
[0022]
[0031] This disclosure relates, in general terms, to alkali metal-containing devices and methods for manufacturing alkali metal-containing devices. More specifically, this disclosure relates to device stacks including lithium metal anodes and pre-lithiumized anodes for energy storage devices, and methods for manufacturing them.
[0023]
[0032] Energy storage devices such as lithium-ion batteries and sodium-ion batteries generally consist of a positive electrode (e.g., cathode) and a negative electrode, with the negative electrode separated by a polymer separator containing a liquid electrolyte. Solid-state batteries also typically consist of a positive electrode (e.g., cathode) and a negative electrode (e.g., anode), but replace both the polymer separator and the liquid electrolyte with ion-conducting materials. Lithium metal is considered one of the most attractive candidates due to its higher capacity and lower potential than conventionally used graphite, but cycle life is a challenge because lithium dendrites form during charging / discharging. The potential of using alkali metals such as lithium and sodium in next-generation batteries such as Li-ion batteries, sodium-ion batteries, and solid-state batteries is becoming increasingly important. However, alkali metal technology presents significant device integration challenges, including the need to handle lithium in a dry chamber environment, appropriate surface protection techniques, and the need to suppress or eliminate lithium metal dendrites during battery cycling. For example, lithium metal is highly reactive with ambient gases such as O2, N2, and H2O under normal atmospheric conditions. From the perspective of electrochemical devices, interface materials should not only help prevent oxidation of the lithium surface but also improve device performance.
[0024]
[0033] By using the implementations described herein, lithium metal deposited on one or both sides can be protected during reel winding and unwinding downstream. The deposition of one or more thin protective films as described herein offers several advantages. In some implementations, one or more protective films described herein provide sufficient surface protection for transport, handling, and storage, while avoiding lithium surface reactions during device integration. In some implementations, one or more protective films described herein are compatible with lithium ions and reduce resistance to ion movement. In some implementations, one or more protective films described herein are ion-conductive and can therefore be incorporated into the formed energy storage device. In some implementations, one or more protective films described herein help suppress or remove lithium dendrites, particularly during high current density operation. In some implementations, the use of protective films described herein reduces the complexity of the manufacturing system and ensures compatibility with existing manufacturing systems.
[0025]
[0034] As described herein, flexible substrates are considered to include, among other things, films, foils, webs, strips of plastic material, metals, paper, or other materials. Typically, terms such as “web,” “foil,” “strip,” and “substrate” are used synonymously.
[0026]
[0035] Figure 1 is a schematic cross-sectional view of an energy storage device 100 incorporating an anode electrode structure having a protective film stack formed according to the implementation described herein. The energy storage device 100 may be a solid energy storage device, a sodium ion-based storage device, or a lithium ion-based energy storage device. Although the energy storage device 100 is shown as a planar structure, it may also be formed into a cylindrical shape by rolling a stack of layers, and furthermore, other cell configurations (e.g., prismatic cells, button-shaped cells, or stacked electrode cells) may be formed. The energy storage device 100 comprises an anode electrode structure 110 and a cathode electrode structure 120, with a separator film 130 positioned between them. In embodiments where the energy storage device 100 is a solid energy storage device, the separator film 130 is replaced by a solid electrolyte film. The cathode electrode structure 120 comprises a cathode current collector 140 and a cathode film 150. The anode structure 110 comprises an anode current collector 160, an anode film 170, and a protective film stack 180. The protective film stack 180 includes at least one or more of the following: a lithium salt film, a sodium salt film, a metal film (e.g., a bismuth film, a tin film, a silver film), and a lithium carbonate film.
[0027]
[0036] The cathode electrode structure 120 includes a cathode current collector 140 and a cathode film 150 formed on the cathode current collector 140. It should be understood that the cathode electrode structure 120 may include other elements or films.
[0028]
[0037] The separator membrane 130 may include, for example, a cellulosic substrate such as a mixture of cellulose nanofibers and aramid fibers. The separator membrane 130 may also include, for example, a microporous polymer separator containing a polyolefin. The polyolefin may be a homopolymer (derived from a single monomer component) or a heteropolymer (derived from multiple monomer components) and may be linear or branched. When the heteropolymer is derived from two monomer components, the polyolefin can take any copolymer chain arrangement, such as a block copolymer or a random copolymer. Similarly, when the polyolefin is a heteropolymer derived from three or more monomer components, it may be a block copolymer or a random copolymer. In certain implementations, the polyolefin may be polyethylene (PE), polypropylene (PP), a blend of PE and PP, or a multilayer porous membrane of PE and / or PP. Commercially available polyolefin porous membranes include CELGARD® 2500 (single-layer polypropylene separator) and CELGARD® 2320 (triple-layer polypropylene / polyethylene / polypropylene separator), available from Celgard LLC. The separator film 130 may be a web-based substrate, or may include one.
[0029]
[0038] The current collectors 140 and 160 on the cathode film 150 and anode film 170, respectively, may be the same or different electron conductors. In some implementations, at least one of the current collectors 140 and 160 is a flexible substrate. In some implementations, the flexible substrate may be a CPP film (i.e., cast polypropylene film), an OPP film (i.e., oriented polypropylene film), or a PET film (i.e., oriented polyethylene terephthalate film). Alternatively, the flexible substrate may be pre-coated paper, a polypropylene (PP) film, a PEN film, a polylactic acid acetate (PLA) film, or a PVC film. Examples of metals that may constitute the current collectors 140 and 160 include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, clad materials, alloys thereof, and combinations thereof. In one or more mountings, which can be combined with other mountings, at least one of the current collectors 140, 160 is perforated. In one mounting, at least one of the current collectors 140, 160 is a metallized plastic substrate including a polymer substrate coated with a metallic material (e.g., polyethylene terephthalate ("PET")). In one or more mountings, which can be combined with other mountings, the anode current collector 160 is a polymer substrate coated with copper (e.g., a PET film). In another mounting, the anode current collector 160 is a polymetallic layer on a polymer substrate. The polymetallic layer can be a combination of copper, chromium, nickel, etc. In one or more mountings, which can be combined with other mountings, the anode current collector 160 is a multilayer structure including a copper-nickel clad material. In one or more implementations, which can be combined with other implementations, the multilayer structure comprises a first layer of nickel or chromium, a second layer of copper formed on the first layer, and a third layer formed on the second layer containing nickel, chromium, or both. In one or more implementations, which can be combined with other implementations, the anode current collector 160 is nickel-coated copper. Furthermore, the current collector may have any shape factor (e.g., metal foil, mesh foil, sheet, or plate), shape, and micro / macro structure.
[0030]
[0039] Generally, in prismatic cells, tabs are formed from the same material as the current collector and may be formed during the manufacturing of the stack or added later. In some implementations, the current collector extends beyond the stack, and the portion of the current collector extending beyond the stack may be used as a tab. In one or more implementations, which may be combined with other implementations, the cathode current collector 140 is aluminum. In one or more implementations, which may be combined with other implementations, the cathode current collector 140 includes aluminum deposited on a polymer substrate (e.g., a PET film). In one implementation, the cathode current collector 140 has a thickness of less than 50 μm, more specifically 5 μm, or even more specifically 2 μm. In one implementation, the cathode current collector 140 has a thickness of about 0.5 μm to about 20 μm (e.g., about 1 μm to about 20 μm, about 6 μm to about 18 μm, or about 5 μm to about 10 μm). In one or more implementations, which can be combined with other implementations, the anode current collector 160 is made of copper or contains copper. In one implementation, the anode current collector 160 is made of stainless steel. In one implementation, the anode current collector 160 has a thickness of less than 50 μm, more specifically 5 μm, and even more specifically 2 μm. In one implementation, the anode current collector 160 has a thickness of approximately 0.5 μm to approximately 20 μm (e.g., approximately 1 μm to approximately 10 μm, approximately 2 μm to approximately 8 μm, approximately 6 μm to approximately 18 μm, or approximately 5 μm to approximately 10 μm).
[0031]
[0040] The cathode film 150 or cathode may be any material compatible with the anode and may include interlayer compounds, insert compounds, or electrochemically active polymers. Suitable interlayer materials include, for example, lithium-containing metal oxides, MoS2, FeS2, BiF3, Fe2OF4, MnO2, TiS2, NbSe3, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, V6O 13and V₂O₅. Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline, polythiophene, and the like. The cathode membrane 150 or cathode may be made of layered oxides such as lithium cobalt oxide, olivine such as lithium iron phosphate, or spinel such as lithium manganese oxide. Examples of lithium-containing oxides include layered oxides such as lithium cobalt oxide (LiCoO₂), or LiNi x Co 1-2x MnO₂ (wherein x is zero or a non-zero number), LiNiMnCoO₂ ("NMC"), LiNi 0.5 Mn 1.5 O₄, Li(Ni 0.8 Co 0.15 Al 0.05 )O₂, mixed metal oxides such as LiMn₂O₄, and doped lithium-rich layered materials. Examples of phosphates include iron olivine (LiFePO₄) and variants thereof (LiFe (1-x) Mg x PO₄ (wherein x is zero or a non-zero number), etc.), LiCoPO₄, LiNiPO₄, Li₃V₂(PO₄)₃, LiVOPO₄, LiMP₂O₇, or LiFe 1.5 P₂O₇. Exemplary fluorophosphates may be LiVPO₄F, LiAlPO₄F, Li₅V(PO₄)₂F₂, Li₅Cr(PO₄)₂F₂, Li₂CoPO₄F, or Li₂NiPO₄F. Exemplary silicates may be Li₂FeSiO₄, Li₂MnSiO₄, or Li₂VOSiO₄. An exemplary non-lithium compound is Na₅V₂(PO₄)₂F₃.
[0032]
[0041] Anode electrode structure 110 includes an anode current collector 160 having an anode membrane 170 formed on the anode current collector 160. The anode electrode structure 110 includes a protective membrane stack 180 including at least one or more of a lithium salt membrane, a sodium salt membrane, a metal membrane, and a lithium carbonate membrane. In some implementations, the one or more protective membranes are ion-conductive membranes.
[0033]
[0042] The anode film 170 may be made of any material compatible with the cathode film 150. The anode film 170 may be or contain alkali metals, alkaline earth metals, and alloys thereof. The anode film 170 may have an energy capacity of 372 mAh / g or more, preferably ≥700 mAh / g, and most preferably ≥1000 mAh / g. The anode film 170 may consist of graphite, silicon, silicon-containing graphite, silicon oxide, alkali metals (e.g., alkali metal foil or alkali metal alloy foil (e.g., lithium aluminum alloy or sodium aluminum alloy)), or mixtures of alkali metals and / or alkali metal alloys with materials such as carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, oxides thereof, or combinations thereof. The alkali metal or alloy includes alkali metals, e.g., lithium metal, sodium, potassium, rubidium, cesium, francium, alloys containing alkali metals, or combinations thereof. The already formed anode material may include, but is not limited to, graphite, silicon, silicon graphite, silicon oxide graphite, silicon, tin, hard carbon, metal oxides, or combinations thereof. Alloys containing alkali metals may include alkali metal alloys and the anode material. Suitable lithium-containing metal films include lithium metal, lithium metal foil, lithium alloy foil (e.g., lithium aluminum alloy), or mixtures of lithium metal and / or lithium alloy with materials such as carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, oxides thereof, or combinations thereof. Suitable sodium-containing metal films include sodium metal, sodium metal foil, sodium alloy foil (e.g., sodium aluminum alloy), or mixtures of sodium metal and / or sodium alloy with materials such as carbon (e.g., coke, graphite), nickel, copper, tin, indium, tellurium, silicon, oxides thereof, or combinations thereof. The anode film 170 may contain an interlayer compound containing lithium and sodium, or an insertion compound containing lithium or sodium.In one or more implementations, which can be combined with other implementations, the anode film is a lithium metal film or a sodium metal film. In some implementations where the anode film 170 contains lithium metal or sodium metal, the lithium metal or sodium metal may be deposited using the methods described herein.
[0034]
[0043] In one implementation, the anode film 170 has a thickness of approximately 10 μm to approximately 200 μm (for example, approximately 1 μm to approximately 100 μm, approximately 10 μm to approximately 30 μm, approximately 20 μm to approximately 30 μm, approximately 4 μm to approximately 20 μm, or approximately 50 μm to approximately 100 μm).
[0035]
[0044] In one or more implementations, which can be combined with other implementations, the anode electrode structure further includes a lithium-activated tellurium film. The lithium-activated tellurium film can be used in place of the anode film 170 to form an anode-less energy storage device. The lithium-activated tellurium film can be an ultrathin lithium-activated tellurium film.
[0036]
[0045] In some implementations, the protective film stack 180 is formed on the anode film 170. In some implementations, one or more protective films are ion-conductive films. In some implementations, the protective film stack 180 is permeable to at least one of lithium ions and lithium atoms. The protective film stack 180 provides surface protection for the anode film 170, thereby enabling handling of the anode film in a drying chamber. In some implementations where the energy storage device 100 is a solid energy storage device, the protective film stack 180 contributes to the formation of an improved SEI layer and thus improves device performance. The protective film stack 180 can be deposited directly on the anode film 170 by physical vapor deposition (PVD) such as evaporation (e.g., thermal or electron beam) or sputtering, atomic layer deposition (ALD), slot die process, immersion coating, planar flow melting spin process, thin film transfer process, gravure coating, or three-dimensional lithium printing process.
[0037]
[0046] In some implementations, the protective film stack 180 includes one or more metal films. Suitable metal films include, but are not limited to, tin films, bismuth films, gallium films, germanium films, copper films, silver films, gold films, bismuth alloy films, gallium alloy films, germanium alloy films, copper alloy films, silver alloy films, gold alloy films, or combinations thereof. One or more metal films may be ultrathin metal seed films.
[0038]
[0047] In some implementations, the protective film stack 180 includes one or more lithium salt films. The lithium salt film includes, or may include, an electrolyte containing a lithium salt, a lithium salt anode coating, or a combination thereof. The electrolyte may be in a gel or polymer matrix medium. The lithium salt film includes, or may include, lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof. Suitable lithium halide films may include, or may be, lithium chloride films, lithium iodide films, lithium fluoride films, and lithium bromide films. Suitable examples of lithium halide films include LiF, LiCl, LiBr, LiI, Li2BeF4, Li3AlF6, Li3YBr6, Li3InCl6, Li3ScCl6, Li6PS5I, Li6PS5Br, Sr2LiCBr3N2, Li3InCl6, LiErCl6, Li6PS5Cl, LiAlCl4, LiGaBr4, LiGaCl4, LiBiF4, Li6AsS5I, LiSbF4, LiHoGe2(O4F)2, LiBF4, or combinations thereof. Suitable examples of lithium oxide films include Li7La3Zr2O12(LLZO), Li7La3Hf2O12, LiErO2, LiYO2, LiLaO2, Li5AlO4, Li6PClO5, Li3AsO4, Li3PO4, Li4GeO4, Li5GaO4, Li2CO3, LiAlB2O5, Li3BiO3, LiZr2(PO4)3, LiTi2(PO4)3, Li2O, Li2HIO, Li10SiP2O12(LiSiPO), LSnPO, or combinations thereof.Suitable examples of lithium sulfide films include Li9S3N, LiAlS2, Li10Si(PS6)2, Li10SiP2S12, Li3AsS3, Li4GeS4, Li3PS4, Li3BS3, Li4TiS4, LiZnPs4, Li7P3S11, Li3PS4, Li4GeS4, Li10GeP2S12, Li2S, SrLi(BS2)3, Li5B7S13, LiSO3F, Li2BS3, Li2B2S5, LiSmS2, KLiS, RbLiS, BaLiS3, Li2GePbS4, LiErS2, LiHoS2, LiDyS2, LSiPS, lithium phosphide (75Li2S-25P2S5 / β-Li3PS4), crystalline LPS (c-LPS), amorphous lithium phosphide LPS (a-LPS), or combinations thereof may be included. Suitable examples of lithium chalcogenide films include Li2Se, LiGaSe2, Li4SnSe4, LiInSe2, LiErSe2, or combinations thereof. Suitable lithium borohydride membranes may include LiBH4·CH3NH2, LiBH4·NH3, LiBH4·NH3BH3, [Li(CH3NH2)(BH4)3], 0.7Li(CB9H10)-0.3Li(CB11H12), or combinations thereof. Other suitable examples of lithium metal salts include Li3BN2, Sr4Li(BN2)3, Li5SiP3, LiMgB3(H9N)2, bis(fluorosulfonyl)imide lithium (LiFSI), bis(trifluoromethanesulfonyl)imide lithium, bis(oxalate)borate lithium (LiBOB), lithium hexafluoride phosphate (LiPF6), or combinations thereof.
[0039]
[0048] In one or more embodiments, LiTFSI can be incorporated into a flexible solid electrolyte (CSE) membrane comprising a poly(vinylidene fluoride) (PVDF) matrix, a high-concentration lithium salt (LiTFSI), a solvent (DMF), and a ceramic filler Li1.3Al0.3Ti1.7(LATP)PVDF-xLiTFSI, HFP / LiTFSI.
[0040]
[0049] In one or more implementations that can be combined with other implementations, the lithium metal salt film may be formed directly on the substrate stack, for example, directly on a current collector to form an anodeless energy storage device.
[0041]
[0050] In some implementations, the protective film stack 180 includes one or more sodium salt films. In one or more implementations that can be used with other implementations, the lithium metal salt film can be replaced with or used in combination with a sodium salt-containing electrolyte, a sodium salt anode coating, or a combination thereof. The sodium salt film is or may contain a nidoborate / closoborate mixed anionic electrolyte. Suitable examples of nidoborate / closoborate mixed anionic electrolytes include NaB11H14, Na(B11H14)(B12H12)2, Nax+2y(B11H14)x(B12H12)y, Na5(B11H14)(B12H12)2, Na4(B11H14)2(B12H12), Na3(B11H14)(B12H12), Na2B12H12, or mixtures thereof, or may include them or mixtures thereof.
[0042]
[0051] In some implementations, each layer of the protective film stack 180 is a coating or discrete film having a thickness in the range of 1 nanometer to 3,000 nanometers (e.g., 10 nanometers to 600 nanometers; 50 nanometers to 100 nanometers; 50 nanometers to 200 nanometers; 100 nanometers to 150 nanometers). In some implementations, each layer of the protective film stack 180 is a coating or discrete film having a thickness of 500 nanometers or less (e.g., approximately 1 nm to approximately 400 nm; approximately 25 nm to approximately 300 nm; approximately 50 nm to approximately 200 nm; approximately 100 nm to approximately 150 nm; approximately 10 nm to approximately 80 nm; or approximately 30 to approximately 60 nanometers). In some implementation configurations, each layer of the protective film stack 180 is a coating or discrete film with a thickness of 100 nanometers or less (e.g., approximately 5 nanometers to approximately 100 nanometers; approximately 5 nanometers to approximately 40 nanometers; approximately 10 nanometers to approximately 20 nanometers; or approximately 50 nanometers to approximately 100 nanometers).
[0043]
[0052] Figure 2 shows a cross-sectional view of one implementation of the anode electrode structure 200 formed by the implementation described in this document. In Figure 2, the anode current collector 160 is shown extending beyond the stack, although it does not need to, and it should be noted that the portion extending beyond the stack can be used as a tab. Although the anode electrode structure 200 is shown as a double-sided electrode structure, it should be understood that the implementation described herein is also applicable to single-sided electrode structures.
[0044]
[0053] The anode electrode structure 200 includes an anode current collector 160 and anode film stacks 110a to 110b formed on opposite sides of the anode current collector 160. In one or more mounting configurations, which can be combined with other mountings, the anode film stacks 110a to 110b include anode films 170a to 170b and protective film stacks 180a to 180b formed on each anode film 170a to 170b.
[0045]
[0054] Figure 3 shows a flowchart of Method 300 for manufacturing an anode electrode structure 400, relating to one or more implementations of the present disclosure. Figures 4A to 4D show diagrams of the various stages of manufacturing an anode electrode structure 400, relating to one or more implementations of the present disclosure. Although Figures 4A to 4D are described in relation to Method 300, it should be understood that the structures disclosed in Figures 4A to 4D are not limited to Method 300 and may instead be independent structures separate from Method 300. Similarly, although Method 300 is described in relation to Figures 4A to 4D, it should be understood that Method 300 is not limited to the structures disclosed in Figures 4A to 4D and may instead be independent of the structures disclosed in Figures 4A to 4D. Figures 4A to 4D show only partial schematic diagrams of the anode electrode structure 400, and it should be understood that the anode electrode structure 400 may include any number of additional layers and / or additional materials common to energy storage devices, which are not shown for brevity. Furthermore, while the method 300 shown in Figure 3 is described in order, it should be noted that other process sequences, including one or more operations, that are omitted and / or added, and / or rearranged in a different preferred order, are also included within the scope of implementation of the disclosures provided herein.
[0046]
[0055] Referring to Figure 4A, in operation 310, a flexible substrate stack 402 is provided. The flexible substrate stack 402 may include one or more layers. In some implementations, for example, in the case of a lithium metal anode device, the flexible substrate stack 402 may include a current collector such as a current collector 160. In some implementations, for example, in the case of a prelithiation process, the flexible substrate stack 402 may include an anode material. In other implementations, in the case of a prelithiation process, the flexible substrate stack 402 may include both a current collector and an anode material. In yet another implementation, the flexible substrate stack 402 may be, or include a separator, for example, the separator film 130 shown in Figure 1. The flexible substrate stack 402 may be, or include a current collector or current collector having an anode material formed on top. The flexible substrate stack 402 may further include an interface layer, a solid electrolyte interface (SEI) layer, or both an interface layer and an SEI layer. In one or more implementations, which can be combined with other implementations, the flexible substrate stack 402 includes a web-based substrate, for example, the current collector may be a web-based substrate.
[0047]
[0056] Referring to Figure 4A, in operation 320, a lithium metal film 404 is formed on the substrate. The lithium metal film 404 can be an anode film 170. In one implementation, the lithium metal film 404 is the anode film, and the flexible substrate stack 402 is the anode current collector. In one implementation, the lithium metal film 404 is formed on the copper current collector. In some implementations, if an anode film is already present on the substrate, the lithium metal film 404 is formed on the anode film. If an anode film is not present, the lithium metal film 404 can be formed directly on the flexible substrate stack 402. Any suitable lithium metal film deposition process for depositing a thin film of lithium metal can be used for the deposition of the lithium metal film. The deposition of the lithium metal film can be done by a PVD process such as evaporation (e.g., thermal evaporation or electron beam), a slot die process, a transfer process, a spin spray coating process following optional melt reflow, or a three-dimensional lithium printing process. The chamber for depositing the lithium metal thin film may include a PVD system such as an electron beam evaporator, thermal evaporator, or sputtering system, a thin film transfer system (including a large-area pattern printing system such as a gravure printing system), or a slot die deposition system. The lithium metal film 404 can be deposited under vacuum. The lithium metal film 404 can also be deposited under vacuum in a roll-to-roll deposition system.
[0048]
[0057] Referring to Figure 4B, optionally, in operation 330, the first protective film 410 is formed on or on the lithium metal film 404. The first protective film 410 may be part of the protective film stack 180, and the lithium metal film 404 may be the anode film 170. In one or more implementations, which can be combined with other implementations, the first protective film 410 is a passivation film. The passivation film can function as a protective film for the lithium metal film 404. For example, the passivation layer can protect the lithium metal film 404 from oxidation and damage during storage and transport. In one or more implementations, which can be combined with other implementations, the first protective film 410 is or includes a lithium carbonate film. In some implementations, the lithium metal film 404 is formed in a first processing chamber and then transferred to a second processing chamber to form an additional film in the stack, whereupon the lithium carbonate film acts as a passivation layer, thereby protecting the underlying lithium metal film 404 from exposure to the atmosphere. In some implementations, where the lithium metal film 404 is not exposed to the atmosphere, the first protective film 410 may not be present. In some implementations, the first protective film 404 has a thickness of 100 nanometers or less (e.g., about 5 to 100 nanometers; about 10 to 20 nanometers; or about 50 to 100 nanometers). The lithium carbonate film can be formed by exposing the lithium metal film 404 to carbon dioxide in the processing chamber where the lithium metal film 404 is formed.
[0049]
[0058] Referring to Figure 4C, in operation 340, the second protective film 420 is formed on or on the lithium metal film 404. The second protective film 420 may also be part of the protective film stack 180. The second protective film 420 may be formed on or on the first protective film 410, if the first protective film 410 is present. In one or more implementations where the first protective film 410 is not present, the second protective film 420 may be formed directly on the lithium metal film 404. In one or more implementations, the second protective film 420 is a metal film or includes a metal film. In one or more implementations, which may also be combined with other implementations, the metal film is a bismuth film, a tin film, a silver film, or a combination thereof. In some implementations, the metal film is an ultrathin metal film. Any suitable metal film deposition process for depositing a thin film of metal may be used to deposit the metal film. Metal films can be deposited by PVD processes such as evaporation (e.g., thermal or electron beam), CVD processes, slot die processes, transfer processes, or three-dimensional lithium printing processes. Chambers for depositing metal films may include PVD systems such as electron beam evaporators, thermal evaporators, or sputtering systems, thin-film transfer systems (including large-area pattern printing systems such as gravure printing systems), or slot die deposition systems. In a particular implementation, the second protective film 420 is a bismuth film formed by a thermal evaporation process.
[0050]
[0059] In some implementations, the second protective film 420 has a thickness of 500 nanometers or less (e.g., approximately 10 nm to 500 nm; approximately 25 nm to 500 nm; approximately 50 nm to 500 nm; approximately 50 nm to 300 nm; approximately 100 nm to 150 nm; approximately 10 nm to 80 nm; or approximately 30 nm to 60 nanometers). In some implementations, the second protective film 620 has a thickness of 100 nanometers or less (e.g., approximately 5 nanometers to 100 nanometers; approximately 10 nanometers to 20 nanometers; or approximately 50 nanometers to 100 nanometers).
[0051]
[0060] Referring to Figure 4D, in operation 350, a third protective film 430 is formed on or above the second protective film 420. The third protective film 430 may be part of a protective film stack 180. In one or more implementations, the third protective film 430 is an alkali metal-containing salt film, e.g., a lithium salt film or a sodium salt film. Any suitable alkali metal salt film deposition process for depositing a thin film of an alkali metal salt can be used to deposit the alkali metal salt film. The deposition of the metal film can be done by a PVD process such as evaporation (e.g., thermal or electron beam), a CVD process, a slot die process, a transfer process, or a three-dimensional lithium printing process. The chamber for depositing the metal film may include a PVD system such as an electron beam evaporator, a thermal evaporator, or a sputtering system, a thin film transfer system (including a large-area pattern printing system such as a gravure printing system), or a slot die deposition system. In a particular implementation, the third protective film 430 is a lithium fluoride film formed by a thermal evaporation process.
[0052]
[0061] In one or more implementations, which can be combined with other implementations, the third protective film 430 may be formed directly on the flexible substrate stack 402, for example, directly on the current collector, to form an anodeless energy storage device.
[0053]
[0062] In some implementations, the third protective film 430 has a thickness of 500 nanometers or less (e.g., approximately 10 nm to 500 nm; approximately 25 nm to 500 nm; approximately 50 nm to 500 nm; approximately 50 nm to 300 nm; approximately 100 nm to 150 nm; approximately 10 nm to 80 nm; or approximately 30 nm to 60 nanometers). In some implementations, the third protective film 430 has a thickness of 100 nanometers or less (e.g., approximately 5 nanometers to 100 nanometers; approximately 10 nanometers to 20 nanometers; or approximately 50 nanometers to 100 nanometers).
[0054]
[0063] The anode electrode stack may be integrated with a cathode structure, such as a cathode electrode structure 120, a separator, such as a separator film 130, or both, to form an energy storage device, such as the energy storage device 100 shown in Figure 1.
[0055]
[0064] Figure 5 shows a flowchart of Method 500 for manufacturing an energy storage device 600 according to one or more implementations of the present disclosure. Figures 6A to 6F show the various stages of manufacturing an energy storage device 600 according to one or more implementations of the present disclosure. Although Figures 6A to 6F are described in relation to Method 500, it should be understood that the structures disclosed in Figures 6A to 6F are not limited to Method 500 and may instead be independent structures independent of Method 500. Similarly, although Method 500 is described in relation to Figures 6A to 6F, it should be understood that Method 500 is not limited to the structures disclosed in Figures 6A to 6F and may instead be independent of the structures disclosed in Figures 6A to 6F. Figures 6A to 6F show only partial schematic diagrams of the energy storage device 600, and it should be understood that the energy storage device 600 may include any number of additional layers and / or additional materials common to energy storage devices, which are not shown for brevity. Furthermore, while the method 500 shown in Figure 5 is described in order, it should be noted that other process sequences, including one or more operations, that are omitted and / or added, and / or rearranged in a different preferred order, are also included within the scope of implementation of the disclosures provided herein.
[0056]
[0065] Referring to Figure 6A, in operation 510, a flexible support layer stack 602 is provided. The flexible support layer stack 602 includes a flexible support layer 610. The flexible support layer 610 has a front side 610f (also referred to as the front) and a back side 610b (also referred to as the back) opposite to the front side 610f. The flexible support layer 610 may contain any suitable material that is suitable for the target processing conditions. In some implementations, the flexible support layer 610 contains multiple sub-layers. In one or more implementations, which may also be combined with other implementations, the flexible support layer 610 may be or contain one or more layers selected from plastics, polymer materials, metallized plastics, metals, paper, multilayers thereof, or combinations thereof. Suitable polymer materials include polymer materials that are transparent to laser light and have low to no photon absorption to prevent overheating and fire. Examples of suitable polymer materials include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide (PI), poly(methyl methacrylate) (PMMA), cellulose triacetate (TAC), polypropylene (PP), polyethylene (PE), polycarbonate (PC), multilayers thereof, or combinations thereof. In one or more mountings, which can also be combined with other mountings, the flexible support layer 610 is a web-based substrate.
[0057]
[0066] In one or more implementations, which can be combined with other implementations, the flexible support layer 610 has a thickness in the range of approximately 1 micron to approximately 100 microns, or in the range of approximately 1 micron to approximately 100 microns, or in the range of approximately 10 microns to approximately 50 microns, or in the range of approximately 25 microns to approximately 50 microns.
[0058]
[0067] The flexible support layer stack 602 may further include a release layer 620. As shown in Figure 6A, the release layer 620 may be formed on the front side 610f of the flexible support layer 610. The release layer 620 has a front side 620f (also referred to as the front) and a back side 620b (also referred to as the back) opposite to the front side 620f. In one or more configurations, the release layer 620 is deposited on the front side 610f of the flexible support layer 610 such that the back side 620b of the release layer 620 is in contact with the front side 610f of the flexible support layer 610. Any suitable process may be used to form the release layer 620 on the front side of the flexible support layer 610. The release layer 620 may be deposited using a non-vacuum coating technique, such as a coating technique performed in air. In one or more configurations, which may also be combined with other configurations, the release layer 620 and the flexible support layer 610 are prefabricated.
[0059]
[0068] The release layer 620 may be or include any material suitable for releasing material subsequently formed from the flexible support layer 610 during a substrate-independent direct transfer (SIDT) process. The release layer 620 may be or include polymer release layers (e.g., plastics, silicones, polymethyl acrylate (PMA), polyethylene terephthalate (PET), carbon fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc.), poly(olefin sulfone), organic materials, inorganic materials, or other materials. In some implementations, which may be combined with other implementations, the release layer 620 may include one or more nanosheets, such as one or more two-dimensional (2D) materials. In one or more implementations, which may be combined with other implementations, the release layer may have a thickness of about 1 nm to about 500 nm, for example, about 10 nm to about 300 nm, for example, about 50 to about 200 nm. In some implementations, the release layer comprises multiple sublayers, each having a thickness of approximately 5 nm or less. Organic or polymer-based release layers can be deposited using wet chemical coating processes, e.g., slot die coating, comma bar coating, or gravure coating, or the vacuum deposition techniques described. The release layer 620 may be or contain inorganic materials, e.g., BN, AlOx, AlOOH, Al, or combinations thereof. In certain implementations, the release layer 620 may include a multilayer structure, e.g., an Al / AlOx / AlOOH multilayer structure. Inorganic-based release layers can be deposited using vapor deposition techniques, e.g., PVD techniques such as sputter deposition and electron beam deposition.
[0060]
[0069] In one or more implementations, the melting points of each layer are equal and / or decrease with each additional layer, with the flexible support layer 610 having the highest melting point, the release layer 620 having a lower melting point than the flexible support layer 610, and subsequent layers having lower melting points.
[0061]
[0070] Referring to Figure 6B, in operation 520, the third protective film 430 is formed on the flexible support layer stack 602. In one or more implementations where a release layer 620 is present, the third protective film 430 may be formed directly on the release layer 620. In one or more implementations, as shown in Figure 6B, the third protective film 430 is formed directly on the front side 620f of the release layer 620. In one or more implementations where a release layer 620 is absent, the third protective film 430 may be formed directly on the front side 610f of the flexible support layer 610. The third protective film 430 may be a lithium salt film or a sodium salt film as described herein. In one or more implementations, operation 520 includes a thermal evaporation process for forming the third protective film 430.
[0062]
[0071] Referring to Figure 6C, in operation 530, the second protective film 420 is formed on the flexible support layer stack 602. In one or more implementations where a third protective film 430 is present, the second protective film 420 may be formed directly on the third protective film 430. The second protective film 420 may be a metal film as described herein. In one or more implementations, operation 530 includes a thermal evaporation process for forming the second protective film 420. The third protective film 430 and the second protective film 420 form a protective film stack 604.
[0063]
[0072] Referring to Figure 6D, in operation 540, an alkali metal-containing layer, for example, a lithium metal film 404, is formed on the flexible support layer stack 602 and the protective film stack 604. The lithium metal film 404 includes a front side 404f (also referred to as the front) and a back side 404b (also referred to as the back) opposite to the front side 404f. In one or more implementations where a release layer 620 is present, the lithium metal film 404 may be formed directly on the release layer 620. In one or more implementations, as shown in Figure 6D, the lithium metal film 404 is formed directly on a second protective film 420. The lithium metal film 404 may be lithium or may contain lithium. In one or more implementations, operation 540 includes an evaporation process for forming the lithium metal film 404. The evaporation process may be an electron beam evaporation process or a thermal evaporation process.
[0064]
[0073] In one or more implementations, the lithium metal film 404 may be part of the SIDT film stack 635. Referring to Figure 6D, the SIDT film stack 635 is shown to include only the lithium metal film 404 and the protective film stack 604, but the SIDT film stack 635 typically includes additional layers, such as additional protective layers, interface layers, and solid electrolyte interface (SEI) layers. When the SIDT film stack 635 is present, the lithium metal film 404 is typically deposited last when forming the SIDT film stack 635. Depositing the lithium metal film 404 last allows the SIDT film stack 635 to be formed without damaging the lithium metal film 404, which typically has a lower melting point than other materials formed within the energy storage device. Conventional methods for forming energy storage devices typically involve the direct deposition of molten lithium onto a current collector in lithium metal anode formation, or onto an anode material in pre-lithified packaging. These methods further include maintaining the underlying substrate when the lithium metal film 404 is formed to prevent damage to the lithium. In contrast, the SIDT film stack 635 and the method described herein allow the lithium metal film 404 to be formed last, before the SIDT film stack 635 is transferred from the flexible support layer stack 602 to the flexible substrate stack 640.
[0065]
[0074] In one or more implementations, which can be combined with other implementations, the solid electrolyte interface (SEI) layer can be optionally included within the SIDT membrane stack 635. In some implementations, the solid electrolyte interface layer can contain or be a metal salt, such as the lithium salts described. The lithium salt can be one or more of the following: LiPF6, LiAsF6, LiCF3SO3, LiN(CF3SO3)3, LiBF6, LiClO4BETTE electrolyte, or a combination thereof. The electrolyte can be in a gel or polymer matrix medium. In one or more implementations, the solid electrolyte interface layer is made of fluorine-based compounds (PTFE, PVDF), LiF, Li2CO3, MgO, AlOx, AlHO2, RENiO3 (RE = rare earth element), BN, BaTiO3, Li4Ti5O12, ZrO2, TiO2, silicon-doped lithium tantalum phosphate, e.g., Li(1+x)Ta2P(1-x)SixO8, Li1.5Ta2P0.5Si0.5O8, lithium tantalum phosphate, e.g., LiTa2PO8 (LTPO The material may be selected from or contain combinations thereof, such as Li2Ta2SiO8 (LTSO), Li0.34La0.56TiO3, lithium aluminum titanium phosphate, for example Li1.3Al0.3Ti1.7(PO4)3 (LATP), lithium aluminum germanium phosphate, for example Li1.3Al0.3Ge1.7(PO4)3 (LAGP), garnet Li7La3Zr2O12 (LLZO), or other materials.
[0066]
[0075] In one or more implementation configurations, which can also be combined with other implementations, the interface layer may optionally be included in the SIDT film stack 635. The interface layer may include at least one of the following: an interface dielectric material, a plating and stripping accelerating layer, and a lithiophilic layer. The interface layer is deposited under vacuum. The interface layer may be deposited under vacuum in a roll-to-roll deposition system. The interface dielectric layer may be selected from AlOx, AlOOH, LiF, BaTiO3, ZrO2, TiO2, Li4Ti5O12, LiAlO2, AlF3, BiF3, AgFx, rare earth (RE) nickelates, RENiO3, or combinations thereof. RE may be a trivalent rare earth. RE may be a lanthanide. RE may be selected from La, Pr, Nd, Sm, Eu, Gd, Dy, Ho, Er, Y, Lu, or combinations thereof. The plating and stripping accelerating layer may be selected from metals, metal alloys, or metal chalcogenides. The plating and stripping accelerating layer may be selected from metal alloys or chalcogenides of Ag, Bi, Sn, Si, Ga, In, or combinations thereof. Deposition of alkali metals or their alloys, for example, lithium metal or its alloys. The interface layer and alkali metal layer or their alloys may be deposited without breaking the vacuum.
[0067]
[0076] In one or more implementations, which can be combined with other implementations, the flexible support layer stack 602 and the lithium metal film 404 are prefabricated. In other implementations, the flexible support layer stack 602 is prefabricated, and the lithium metal film 404 is formed on the flexible support layer stack 602 via a deposition process, such as a physical vapor deposition (PVD) process.
[0068]
[0077] After operation 540 and before operation 550, the flexible support layer stack 602 on which the SIDT film stack 635 is formed may be transferred from a vacuum coating system, such as a roll-to-roll coating apparatus, to a lamination transfer apparatus, such as a lamination transfer system. The stack transfer process of operation 540 may include applying the flexible substrate stack 640 to the front side 404f of the lithium metal film 404 and, as shown in Figure 6E, removing the flexible support layer 610 and optionally the release layer 620 from the lithium metal film 404 to form the anode film stack 645.
[0069]
[0078] Referring to Figure 6E, in operation 550, the SIDT film stack 635 is stacked on the flexible substrate stack 640. The flexible substrate stack 640 may contain one or more layers. In some implementations, for example, in the case of a lithium metal anode device, the flexible substrate stack 640 may contain a current collector, such as a current collector 160. In some implementations, for example, in the case of a prelithiation process, the flexible substrate stack 640 may contain an anode material, such as an anode film 170. In other implementations, in the case of a prelithiation process, the flexible substrate stack 640 may contain both a current collector and an anode material. In yet another implementation, the flexible substrate stack 640 may be, or may contain, a separator, such as the separator film 130 shown in Figure 1. The flexible substrate stack 640 may be, or may contain, a current collector or current collector having an anode material formed on top. In one or more implementations that can be combined with other implementations, the flexible substrate stack 640 includes a web-based substrate, for example, the current collector may be a web-based substrate. During the stacking process of operation 550, the lithium metal film 404 of the SIDT film stack 635 is in contact with the flexible substrate stack 640. For example, the front side 404f of the lithium metal film 404 is in contact with the surface of the flexible substrate stack 640, as shown in Figure 6E. In one or more implementations where the flexible substrate stack 640 includes only a current collector, the front side 404f of the lithium metal film 404 is in contact with the surface of the current collector. In one or more implementations where the flexible substrate stack 640 includes an anode material, the front side 404f of the lithium metal film 404 is in contact with the surface of the anode material to pre-lithify the anode material.
[0070]
[0079] Optionally, during operation 550, pressure is applied to one or more of the flexible substrate stack 640 and the flexible support layer stack 602 on which the SIDT film stack 635 is formed, so that the flexible substrate stack 640 is laminated onto the lithium metal film 404. In one or more implementations where method 500 is performed with a roll-to-roll tool, the web tension is sufficient to laminate the lithium metal film 404 onto the flexible substrate stack 640, and no additional pressure is required. In one or more implementations where additional pressure is used to laminate the lithium metal film 404 onto the flexible substrate stack 640, the lamination process includes pressing the lithium metal film 404 onto the flexible substrate stack 640 with a pressure large enough to adhere the lithium metal film 404 to the flexible substrate stack 640 without damaging the lithium metal film 404. In other words, the pressure is such that the lithium metal film 404 is not mechanically destroyed or degraded by cracking, shattering, etc. The pressure may be applied using any suitable technique. In one or more implementations, pressure is applied by the calendering process. For example, pressure may be applied to the back side 610b of the flexible support layer 610 and the back side 640b of the flexible substrate stack 640. In one or more other implementations, pressure is applied by a vacuum source. In one or more other implementations, the pressure is external pressure.
[0071]
[0080] Referring to Figure 6F, in operation 560, the lithium metal film 404 is separated from the flexible support layer stack 602 to form an anode film stack 645, which includes the SIDT film stack 635 formed on the flexible substrate stack 640. In one or more implementations, which can also be combined with other implementations, a portion of the release layer 620 can be transported or partially transferred using the lithium metal film 404. Alternatively, in other implementations, after operation 560, the release layer 620 remains on the flexible support layer 610, or remains partially thereafter.
[0072]
[0081] In operation 570, the anode film stack 645 may be integrated with a cathode structure, such as a cathode electrode structure 120, a separator, such as a separator film 130, or both, to form an energy storage device, such as the energy storage device 100 shown in Figure 1.
[0073]
[0082] Examples:
[0083] The following non-limiting examples are provided to further illustrate the implementations described herein. However, these examples are not intended to cover all implementations described herein, nor to limit their scope.
[0074]
[0084] Lithium metal is highly reactive with ambient gases such as O2, N2, and H2O under normal atmospheric conditions. In the following examples, samples of both unmodified and modified lithium metal were taken out of a drying chamber where the material was stable and left in the ambient environment for 15 minutes. The experimental results showed that the unmodified sample reacted very rapidly upon removal from the drying chamber, exhibiting a deep silver color and eventually changing to black within minutes. This is not surprising, as lithium can react rapidly to form LiOH, Li3N, and Li2CO3, as is known from the literature. On the other hand, the lithium surface modified with the protective layer stack described herein remained stable with minimal degradation / discoloration. The results indicate that the protective layer stack described herein effectively protects the lithium metal from the surroundings. Furthermore, the protective layer stack described herein enables the delivery and transport of the lithium metal film, thereby activating the underlying lithium metal and making it available for electrochemical performance.
[0075]
[0085] Materials: The stacks, including combinations of layers of the tested coating materials, are labeled as Type A (LiF), Type B (Bismuth), Type C (Silver), Type D (Tin), and Type E (LTO). The results are summarized in Table I. Table I shows the tested thickness range and coating method for each material. TIFF2026530460000002.tif98170Table I
[0076]
[0086] Process initiation: The process initiation involved first calibrating the film thickness, followed by the deposition of initial samples. Layered coatings of types A, B, C, D, and E, and of various thicknesses, were deposited on a Li-coated Cu foil (single-sided, with both the Li and Cu foils being 18 μm thick).
[0077]
[0087] Characteristics of the protective layer: SEM images of the initial samples are shown in Figure 7. All samples were exposed to in-situ CO2 treatment, and a thin Li2CO3 film of less than approximately 40 nm was formed on the control samples. In the passivated samples, clear evidence of material coating was observed, with varying degrees of structural morphological change depending on the type of protective layer. In some cases, the outline of the lithium metal was masked. Surface roughness data is shown in Table II. Table II includes the surface roughness parameters of each modified sample and a comparison with the control sample. According to the initial data, no significant increase in the surface roughness of the samples was observed after passivation with the protective stack described above. Coin-type batteries were fabricated and tested to measure the impedance and performance of the batteries. TIFF2026530460000003.tif66170Table II
[0078]
[0088] Formation and testing of coin-shaped cells
[0089] 1cm 2The electrodes were manually perforated using an 11.3 mm diameter punch. The coin-type cells were assembled using SUS3130L nickel-plated caps and cases. In symmetrical cells, the anode is used for both electrodes, but in half-cells, it is used only as the positive electrode, with the counter electrode being 11 μm Li-ion Cu on one side. The electrolyte (1.0 M LiPF6 + 2% FEC in EC / DEC (1:1 v / )), also known as AM-4, was formulated for Applied Materials and used as is. CELGARD® 2500 was used as a separator. The separator was moistened with approximately 3 drops of electrolyte. After assembly, all cells were sealed by pressing them for 2.5 seconds using a standard battery crimping tool.
[0079]
[0090] Electrochemical impedance spectroscopy (EIS) EIS (Bio-Logic) was performed using a symmetrical two-cell configuration, with a 5mV perturbation applied, and scanned in the range of 10MHz to 1MHz. Figure 8 shows the impedance data and impedance Nyquist plots collected for the assembled cells. The stacked designs of types A+B, A+D, and E had the highest total impedance and control values, while type A+C had the lowest. The remaining data falls somewhere in between. The inset in Figure 8 shows the impedance values at a frequency of 150Hz. The green area in the inset in Figure 8 represents the resistance values of the samples (control, type A+C, type B, type C) at 250Ωcm. 2 While the others were below this value, the remaining samples had higher resistance values (>400 ohms / cm²), indicated in red. 2 It belonged to the region of ). Note that the control value and type A+C value were the lowest at all frequencies. Low impedance and high current density (>3mAh / cm²). 2 A good balance of cycle characteristics in ) has been selected as the success criterion.
[0080]
[0092] Electrochemical cycle
[0093] The cells were left to rest for 24 hours before capacity and cycle tests were performed using a MacCohr Series 4600 battery tester. Figure 9 shows the values after 15 minutes of charging: 0.2, 2, and 3 mA / cm². 2 The Li deposition / detachment behavior of a symmetric cell discharged for 15 minutes at a current rate is shown, with upper and lower voltage limits of 1V, which is similar to the required formation cycle. Typical voltage-time profiles of Li plating / release in Li / Li symmetric cells are shown for comparison with a control sample and Type A+C, Type A, Type B, Type C, Type D, and Type D protective coatings. The black line corresponds to the control sample, and the red line corresponds to Type A+C and other samples. Subsequently, tests were performed at the current density required for long-term cycle testing. Figure 10 shows the discharge and charge capacities against the number of cycles collected for the cells. As shown in Figure 10, after approximately 140 charge-discharge cycles, or when the capacity degraded to zero. Type A+B, shown by the green line in Figure 10, showed the best cycle performance of over 100 cycles, while the other types short-circuited earlier. The control sample, shown by the orange line, performed the worst compared to all samples. The current density in the charge-discharge cycle was 3.0 mA / cm². 2 That was the case.
[0081]
[0094] The embodiments of the present disclosure described herein have many advantages. However, this disclosure does not require that all advantageous features and advantages be incorporated into all methods of implementation of the present disclosure.
[0082]
[0095] Certain features (including process steps) of the Disclosure are referenced in the Abstract, Detailed Description, Claims, and Accompanying Drawings. The disclosures herein should be understood to include all possible combinations of such specific functions. For example, if a particular function is disclosed in a particular aspect or implementation of the Disclosure, or in the context of a particular claim, that function may, as far as possible, be used in combination with, or in the context of, other particular aspects and implementations of the Disclosure, and even in the Disclosure as a whole.
[0083]
[0096] The number following the word "at least" is used to indicate the beginning of a range that starts at that number (depending on the variable being defined, this may be a range with an upper limit or a range without an upper limit). For example, "at least one" means one or more. In this text, when the word "maximum" is followed by a number, it is used to indicate the end of a range that ends at that number (depending on the variable being defined, this may be a range with a lower limit of 1 or 0, or a range with no lower limit). For example, "maximum 4" means 4 or less, and "maximum 40%" means 40% or less. In this specification, when a range is indicated as "(first number) ~ (second number)" or "(first number) - (second number)", it means a range where the lower limit is the first number and the upper limit is the second number. For example, 25 ~ 100 mm means a range with a lower limit of 25 mm and an upper limit of 100 mm.
[0084]
[0097] The embodiments and all functional operations described herein can be implemented in digital electronic circuits, computer software, firmware, or hardware (including the structural means disclosed herein and their structural equivalents), or in combination thereof. The embodiments described herein can be implemented as one or more non-temporary computer program products, i.e., one or more computer programs specifically embodied in a machine-readable storage device, and used to be executed by or to control the operation of a data processing device (e.g., a programmable processor, computer, or multiple processors or computers).
[0085]
[0098] The processes and logic flows described herein can be performed by one or more programmable processors executing one or more computer programs to perform operations on input data and generate outputs. These processes and logic flows can also be performed by special-purpose logic circuits such as FPGAs (Field-Programmable Gate Arrays) and ASICs (Application-Specific Integrated Circuits), and such devices can also be implemented.
[0086]
[0099] The term "data processing device" encompasses all devices, machines, and equipment for processing data, including, for example, a programmable processor, a computer, or multiple processors or computers. In addition to hardware, such a device may include code that creates the execution environment for the target computer program, such as processor firmware, a protocol stack, a database management system, an operating system, or one or more combinations thereof. Examples of processors suitable for executing computer programs include both general-purpose and specialized microprocessors, and one or more processors in any type of digital computer.
[0087]
[0100] Computer-readable media suitable for storing computer program instructions and data include all forms of memory, such as non-volatile memory, media, and memory devices. Examples include semiconductor memory devices, such as EPROM, EEPROM, flash memory, and magnetic disks, such as internal hard disks, removable disks, magneto-optical disks, CD-ROMs, and DVD-ROMs. Processors and memory can be complemented or integrated with dedicated logic circuits.
[0088]
[0101] The terms “comprises,” “including,” and “having,” as well as their grammatical equivalents, are used in this text to mean the optional presence of other components, elements, operations, etc. For example, an article “comprising” (or “which comprises)” components A, B, and C may consist only of components A, B, and C (i.e., include only components A, B, and C), or it may include not only components A, B, and C but also one or more other components. Furthermore, when "comprising" or an equivalent grammatical conjunction precedes a composition, element, or group of element, it is understood that a conjunction such as "consisting essentially of," "consisting of," "selected from the group of consisting of," or "is" is expected to precede the description of that composition, element, or group of elements, or vice versa.
[0089]
[0102] Where this specification refers to a method that includes two or more defined operations, the defined operations may be performed in any order or simultaneously (unless the context excludes such possibility), and may include one or more other operations that are performed before any of the defined operations, between two defined operations, or after all of the defined operations (unless the context excludes such possibility).
[0090]
[0103] When describing elements, exemplary aspects, or embodiments of this disclosure, the articles "a," "an," "the," and "said" indicate that there is one or more elements.
[0091]
[0104] The above describes embodiments of the present disclosure, but other embodiments and further embodiments can be devised without departing from the basic scope of the present disclosure, the scope of which will be defined by the claims described below.
Claims
1. Anode electrode structure, A current collector containing copper and / or stainless steel, A lithium metal film formed on the current collector, A protective film stack formed on the lithium metal film, A metal film formed on a lithium metal film, the metal film being selected from a bismuth film, a tin film, a silver film, or a combination thereof, and A lithium salt film formed on the metal film, wherein the lithium salt film is selected from lithium, lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof. A protective film stack including an anode electrode structure containing an anode electrode.
2. The anode electrode structure according to claim 1, wherein the protective film stack further comprises a lithium carbonate film, the lithium carbonate film is formed on a lithium metal film, and the metal film is formed on the lithium carbonate film.
3. The anode electrode structure according to claim 1, further comprising an anode film, wherein the anode film is formed on a current collector, and a lithium metal film is formed on the anode film.
4. The anode electrode structure according to claim 1, wherein the metal film is a silver film.
5. The anode electrode structure according to claim 1, wherein the metal film has a thickness in the range of about 50 nanometers to about 500 nanometers.
6. The anode electrode structure according to claim 5, wherein the lithium salt film is a lithium fluoride film having a thickness in the range of about 100 nanometers to about 500 nanometers.
7. The anode electrode structure according to claim 1, wherein the current collector includes a polymer substrate and a copper film formed on the polymer substrate.
8. An energy storage device, an anode electrode structure according to any one of claims 1 to 7, Cathode electrode structure, A separator membrane or solid electrolyte membrane is formed between the anode electrode structure and the cathode electrode structure. Energy storage devices including
9. A method for forming an anode electrode structure, comprising forming a protective film stack on a lithium metal film, wherein the lithium metal film is formed on a substrate, and the protective film stack is formed on a substrate. Forming a metal film on a lithium metal film, wherein the metal film is selected from a bismuth film, a tin film, a silver film, or a combination thereof, and Forming a lithium salt film on a metal film, wherein the lithium salt film is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof. A method for forming an anode electrode structure that includes [a specific component].
10. The method according to claim 9, further comprising forming a lithium carbonate film on a lithium metal film before forming a protective film stack on a lithium salt film, wherein the lithium carbonate film is formed on the lithium salt film and the metal film is formed on the lithium carbonate film.
11. The method according to claim 10, wherein forming a lithium carbonate film includes exposing a lithium metal film to CO2 gas in a first processing region defined by a first processing chamber.
12. The method according to claim 11, further comprising transferring a substrate from a first processing region to a second processing region defined by a second processing chamber, wherein a protective film stack is formed in the second processing chamber.
13. The method according to claim 9, wherein the substrate is a current collector having an anode film formed on the substrate.
14. The method according to claim 9, wherein the formation of a metal film includes a thermal evaporation process.
15. The method according to claim 14, wherein the formation of the lithium salt film includes a thermal evaporation process.
16. The method according to claim 9, wherein the substrate is a web-based substrate.
17. The method according to claim 9, wherein the metal film is a silver film.
18. The method according to claim 9, wherein the metal film has a thickness in the range of about 50 nanometers to about 500 nanometers.
19. The method according to claim 18, wherein the lithium salt film is a lithium fluoride film having a thickness in the range of about 100 nanometers to about 500 nanometers.
20. The method according to claim 9, wherein the substrate comprises a polymer substrate and a copper film formed on the polymer substrate.
21. A method for forming a membrane stack for an energy storage device, This involves forming a protective film stack on top of a flexible support layer stack, Forming a lithium salt film on the release layer, Forming a metal film on a lithium salt film, wherein the metal film is selected from a bismuth film, a tin film, a silver film, or a combination thereof, and Forming a lithium metal film on the metal film. Forming a protective film stack including, The lithium metal film is laminated onto a flexible substrate stack, In order to form the anode film stack, the protective film stack is separated from the flexible support layer stack. A method comprising a lithium salt film selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof.
22. The method according to claim 21, wherein the flexible support layer stack includes a polymer substrate, the polymer substrate has a release layer formed on the polymer substrate, and the protective film stack is formed on the release layer.
23. The method according to claim 21, wherein the flexible support layer stack includes a polymer substrate and the protective film stack is formed on the polymer substrate.
24. The method according to claim 21, wherein the flexible substrate stack includes a current collector containing copper.
25. The method according to claim 24, wherein the flexible substrate stack further includes an anode film formed on a current collector, and the lithium metal film is in contact with the anode film.
26. The method according to claim 21, wherein the formation of the metal film includes a thermal evaporation process.
27. The method according to claim 26, wherein the formation of a lithium salt film includes a thermal evaporation process.
28. The method according to claim 26, wherein the metal film is a silver film.
29. Anode stack, A copper substrate configured to function as a current collector, A lithium layer is placed on the copper substrate and configured to function as an anode, A silver layer disposed on the lithium layer, A lithium salt layer disposed on the silver layer, wherein the lithium salt layer is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof. an anode stack, including the anode stack.
30. The anode stack according to claim 29, wherein a passivation layer is disposed between the lithium layer and the silver layer.
31. The anode stack according to claim 30, wherein the passivation layer contains lithium carbonate and is formed by passivating the lithium layer with carbon dioxide.
32. The anode stack according to claim 29, wherein the lithium salt layer contains lithium fluoride.
33. The anode stack according to claim 29, wherein the lithium salt layer has a thickness of 50 nm to 600 nm.
34. The anode stack according to claim 29, wherein the silver layer has a thickness of 40 nm to 600 nm.
35. A method for forming an anode stack, Using a roll-to-roll physical vapor deposition (PVD) tool, a lithium layer is deposited on a copper substrate, Using thermal evaporation, a silver layer is deposited on the lithium layer, The method involves depositing a lithium salt layer on the silver layer using thermal evaporation, wherein the lithium salt layer is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof. A method that includes this.
36. A method for forming an anode stack according to claim 35, comprising passivating a lithium layer using an Incitu carbon dioxide passivation process before depositing a silver layer.
37. A method for forming an anode stack according to claim 36, wherein the deposition and passivation of the lithium layer are performed using a roll-to-roll PVD tool, and the deposition of the silver layer and the lithium salt layer are performed in different chambers.
38. A method for forming an anode stack according to claim 35, wherein the method is performed using a roll-to-roll PVD tool.
39. A method for forming an anode stack according to claim 35, wherein the lithium salt layer contains lithium fluoride.
40. A method for forming an anode stack according to claim 35, wherein the lithium salt layer has a thickness of 50 nm to 600 nm.
41. A method for forming an anode stack according to claim 35, wherein the silver layer has a thickness of 40 nm to 600 nm.
42. A method for forming an anode stack according to claim 35, further comprising integrating the anode stack with a separator and a cathode structure in order to form an energy storage device.
43. A method for forming an anode structure, Forming a release layer on a polymer substrate, Depositing a lithium salt layer on a release layer placed on the polymer substrate, Depositing a silver layer on the lithium salt layer, Depositing a lithium layer on a silver layer to form an anode, The process involves transferring an anode from a polymer substrate to a copper substrate to form an anode structure, wherein the lithium salt layer is selected from lithium sulfide, lithium oxide, lithium halide, lithium chalcogenide, lithium borohydride, or a combination thereof, and transferring the anode from a polymer substrate to a copper substrate. A method that includes this.
44. A method for forming an anode stack according to claim 43, wherein the lithium salt layer contains lithium fluoride.
45. A method for forming an anode stack according to claim 43, wherein the lithium salt layer has a thickness of 50 nm to 600 nm.
46. A method for forming an anode stack according to claim 43, wherein the silver layer has a thickness of 40 nm to 600 nm.
47. A method for forming an anode stack according to claim 43, wherein the lithium layer has a thickness of 2 microns to 25 microns.
48. A method for forming an anode stack according to claim 43, further comprising integrating the anode stack with a separator and a cathode structure in order to form an energy storage device.